Compression of Morbidity is Observed Across Cohorts with Exceptional Longevity - Ismail, Khadija (J Am Geriatr Soc, 2016)
OBJECTIVES: To determine if there is a compression of morbidity in a sample of Ashkenazi Jewish centenarians, similar to what has been reported in other cohorts with exceptional longevity. DESIGN: Case control study. SETTING: Longevity Genes Project (LGP) and New England Centenarian Study (NECS). PARTICIPANTS: 439 LGP (mean age: 97.8 ± 2.8) and 1,498 NECS (mean age: 101.4 ± 4.0) participants compared to their respective younger referent cohorts of 696 LGP and 302 NECS controls, respectively. MEASUREMENTS: Self and proxy reports of age of onset of cancer, cardiovascular disease, diabetes mellitus, hypertension, osteoporosis, and stroke. RESULTS: Long-lived individuals from both LGP and NECS compared to their respective younger referent groups delay the age of onset of cancer, cardiovascular disease, diabetes mellitus, hypertension, and osteoporosis. The relative risk of overall morbidity is 0.12 in NECS males and 0.20 in NECS females compared to the younger NECS referents and 0.18 in LGP males and 0.24 in LGP females compared to younger male and female LGP referents. The age at which 20% of each of the centenarian groups experienced specific diseases was significantly delayed by between 18 and 24 years relative to the referent groups, when stratified by sex. CONCLUSION: The similar extension of health-span and compression of morbidity seen in both the NECS and LGP centenarian samples further validates the utility of these rare individuals for the study of factors that delay or prevent a broad spectrum of diseases otherwise associated with mortality and disability.